Childhood-Onset Systemic Lupus Erythematosus in Southwestern Iran: A Clinical and Serological Study - Soheila ALYASIN; Reza AMIN; Mozhgan MOGHTADERI; Sara KASHEF; 1; 2 (Archives of Rheumatology, 2014)
Objectives: This study aims to describe clinical manifestations of systemic lupus erythematosus (SLE) and laboratory assessment in children in the Southwestern Iran. Patients and methods: This descriptive study included 32 patients (23 females, 9 males; mean age 10.5 years; range 3 to 16 years) with SLE who were referred to Rheumatology Outpatient clinic at Shiraz University of Medical Sciences between July 2011 and July 2012. A complete history of each patient was taken and the medical records were reviewed for clinical symptoms and laboratory test results. Results: Twenty-three patients were newly diagnosed with SLE during the study. The most commonly involved organs were skin in 30, joints in 21, kidney in 18 and central nervous system in 10 patients. Laboratory findings at the time of diagnosis showed anemia in 19, leukopenia in 15 and thrombocytopenia in three patients. Increased erythrocyte sedimentation rate and C-reactive protein values were detected in 27 patients and 16 patients, respectively. There was high level of double-stranded DNA in 30 and anti-nuclear antibodies in 27 patients. A total of four patients died within the study period, one from pulmonary hemorrhage, two from end-stage renal disease and the other one due to subdural hematoma and renal failure. Conclusion: Our study results demonstrated that the clinical manifestations of SLE in childhood were mostly consistent with the previous reports of Iran and nearby Arabian countries. Kidney involvement was lower in our study; however with a higher number of patients with antinuclear antibody negative.